Affective commitment of employees designated as talent: signalling perceived organisational support. (2nd January 2015) - Gelens, Jolyn; Dries, Nicky; Hofmans, Joeri; Pepermans, Roland
We examined how perceived organisational support affects the relationship between being designated as talent and affective commitment. Two studies were conducted in two different 'talent' populations. In study one, a questionnaire was distributed within one large company among employees, who were designated as high potential, and a control group, who was not (N = 203). In study two, the same questionnaire was distributed within a different company among employees, who were designated as management trainee, and a control group, who were not (N = 195). The results from both studies showed that perceptions of organisational support were significantly stronger for employees who were designated as talent. Moreover, perceived organisational support mediated the relationship between an employee's designation as talent and affective commitment in both studies. Theoretical and practical implications of these findings are discussed.